Diagnosis and management practices for gestational diabetes mellitus in Australia: Cross‐sectional survey of the multidisciplinary team. (18th April 2018) - Meloncelli, Nina; Barnett, Adrian; Pelly, Fiona; de Jersey, Susan
Abstract : Background: Gestational diabetes mellitus (GDM) is one of the most common pregnancy disorders; however, if well managed, women with GDM experience similar pregnancy outcomes to those without. Currently, there is limited evidence on actual management practices across Australia or how multidisciplinary teams interact to optimise care. Aims: To examine the current screening, diagnostic, task and role perceptions and management practices, as reported by members of the GDM multidisciplinary team. Methods: A 64‐item electronic survey containing multiple choice, Likert scale and open‐ended questions was developed for this cross‐sectional observational study and advertised through health professional organisations and Queensland Health facilities in May and June, 2017. Results: The 183 survey respondents included 45 diabetes educators, 43 dietitians, 21 endocrinologists/diabetes specialists, 14 obstetricians and 21 midwives. Although almost 90% reported using updated diagnostic guidelines, less than two‐thirds used GDM management guidelines. While 68% reported using the same blood glucose targets for GDM management, there was variation to what criteria prompted the commencement of medication to control blood glucose levels. There was a good consensus concerning the health professional responsible for tasks such as medical nutrition therapy, gestational weight gain and self‐blood glucose monitoring education and ultrasound use. Other tasks appeared to be the role of almost any member of the GDM multidisciplinary team. Conclusions: The survey results indicate there is a need for consistent evidence on how to best manage GDM and that role identity, access to specialist knowledge and best practice need to be clearly defined within GDM models of care.